(untitled) (African Journal of Biomedical Research, 2024)
Optimal health is required in endangered species and one of the vital organs to assess the overall health of an animal is the heart. The Electrocardiograph (ECG) provides information on the health status of the heart. There is dearth of information on the electrocardiographic parameters of white bellied pangolins. In this study, we obtained cardiac parameters from clinically healthy white-bellied pangolins (n=26) rescued from trade in Southwestern Nigeria. The Pangolins were sedated with Ketamine hydrochloride (10mg/kg) and Xylazine (3mg/kg). Electrocardiography was recorded with the animal on dorsal recumbence using a 6/7 lead computer ECG machine. Standard bipolar (I, II, III) and augmented unipolar (aVR, aVL and aVF) leads readings were recorded. Measurements are presented as mean±standard deviation. Electrocardiogram (ECG) readings were analysed using Descriptive statistics, Student t-test at 5% level of significance. Electrocardiographic parameters such as heart rate (HR), P-wave duration, PR-interval, QRS duration, QT interval, QTc interval and Ra were recorded for each of the leads. The HR ranged from 54 to 109 beats/min with a mean ± standard deviation of 82.85±13.50 beats/min. Lead II recordings showed a P-wave duration of 61.19±16.73 ms, PR interval 94.88±18.88 ms, QRS duration 50.77±16.05 ms, QT interval 299.88±31.23 ms, QTc interval 347.88±37.07 ms and Ra 1.28±0.38 mV. There were no significant differences in the ECG parameters between male and female white-bellied pangolins in all the leads measured. The findings of this study should provide clinical reference for healthy management of African pangolins. It would also serve as a reference value for further research. .